Implementation of UI/UX Design in the Development of Profile Website Using the User Centered Design Method - Harianty, Savanda; Wahyuni, Sri; Arista, Ruly Dwi (Vertex, 2025)
The evolution of UI/UX design on the profile webpage is covered in this study. A community called Omah Cikal Kreatif aims to empower housewives by fostering their creativity via handicrafts made from secondhand items.  The primary obstacle is the limitations of digital platforms' user interface (UI) design and user experience (UX), which affect user engagement and low exposure. This research aims to design and develop an attractive, informative and easy-to-use website by applying the UCD approach. The development process includes user needs analysis, prototype design, and design evaluation using the System Usability Scale (SUS) method. The results of this research provide strategic insights in improving the quality of website design and strengthening Omah Cikal Kreatif's identity in the digital realm